EKSISTENSI NYEPI SEGARA DALAM UPAYA MENJAGA PELESTARIAN ALAM LINGKUNGAN DAN NILAI SOSIAL BUDAYA DI DESA PED, KECAMATAN NUSA PENIDA, KABUPATEN KLUNGKUNG - I Kadek Widiana (Universitas Pendidikan Ganesha, 2013)
ABSTRACTThis study aimed to determine (1) philosophical foundation of Nyepi Segara, (2) Theimplementation of Nyepi Segara, (3) Nyepi Segara role in maintaining environmentalconservation and socio-cultural values in the village of Ped, Nusa Penida, Klungkung regency.This study, using a qualitative descriptive research approach and data collection techniques thatare used through interviews, observation, literature. The analysis of the data used in this study isto use qualitative descriptive analysis. These subjects include: Indigenous kelihan Ped, PedKadus village, elders (elders) who knows about Nyepi Segara Village Ped. The results of thisstudy indicate that (1) philosophical foundation Nyepi Ped Segara Village is a form of homage tothe god Varuna is believed to be the ruler of oceans and seas. (2) The Nyepi Segara Village Ped,whose implementation falls on the full moon based calendar sasih Kapat Bali, has beenconducted since 1600 AD or during the reign of Dalem Waturenggong. (3) The role of NyepiSegara Village Ped in maintaining environmental conservation and socio-cultural values with TriHita Karana is based include: (a) the harmonious relationship between man and Sang HyangWidhi Wasa, (b) a harmonious relationship between man and man, (c) a harmonious relationshipbetween man and nature. (4) the constraints faced in the implementation Nyepi immediately atPed village, Nusa Penida, Klungkung regency, and alternatf solution.Keywords: Nyepi Segara, preservation of the natural environment and cultural social